(untitled) - Minelli, Michael (Hoboken, N.J., 2007)
CIOs spend more than
Keywords: Giám đốc phòng thông tin,Công nghệ thông tin,Công nghệ thông tin,Chief information officers,Information technology,Information technology; Khía cạnh kinh tế,Quản trị,Economic aspects,Management